Improved substructure synthesis method using experimental modal analysis technique to solve analysis and design problems based on security issues - An, Byung Hun; Lee, Jin Woo (Mechanical Systems and Signal Processing, 2020)
A substructure synthesis method based on frequency response functions is improved to solve a security-issue-based analysis problem and is applied to an optimal design problem for a finished product consisting of two substructures. While geometry information is provided for one substructure, a limited number of frequency response functions are provided for the other substructure instead of its geometry information. The dynamic stiffness matrix of the latter is estimated from the provided frequency response functions using an experimental modal analysis technique. It is combined with the mass and stiffness matrices of the former to predict the vibration natural frequency of a finished product. The improved substructure synthesis method is used to predict the frequency response functions of a T-shaped beam consisting of a doubly clamped beam and a cantilever beam. Additionally, in a vehicle steering module, it is applied to a size optimization problem that is formulated to maximize its natural frequency. Numerical analysis and design results indicate the effectiveness of the improved substructure synthesis method for industrial applications.
Keywords: Doubly clamped beam; Dynamic stiffness matrix; Experimental modal analysis; Finished products; Frequency response functions; Geometry information; Stiffness matrices; Substructure synthesis method; Frequency response function; Natural frequency; Security issue; Size optimization problem; Substructure synthesis method